Gastric cancer incidence and mortality trends 2007–2016 in three European countries - Libânio, Diogo; Rodrigues, Jessica R.; Bento, Maria J.; Ebigbo, Alanna; Messman, Helmut; Verhoeven, Rob H.A.; Van Damme, Nancy; Bisschops, Raf; Spaander, Manon C.W.; Dinis-Ribeiro, Marío (Endoscopy, 2021)
Background Increased awareness of gastric cancer risk, easy access to upper endoscopy, and high definition endoscopes with virtual chromoendoscopy may have led to the increase in early diagnosis of gastric cancer observed in recent years in Europe, which may be associated with improved survival. Currently, no data exist on the impact of early diagnosis on survival at a populational level in Europe. Our aim was to assess gastric cancer incidence, early diagnosis, and survival in northwestern and southern European countries with a low-to-moderate incidence of gastric cancer.Methods Data on 41 138 gastric cancers diagnosed in 2007–2016 were retrieved from national cancer registries of Belgium, the Netherlands, and northern Portugal. Age-standardized incidence and mortality rates were assessed and expressed per 100 000 person-years. Early diagnosis was defined as T1 tumors. Net survival estimates for 2007–2011 vs. 2012–2016 were compared.Results Age-standardized incidence and mortality decreased over time in Belgium, northern Portugal, and the Netherlands (relative incidence decrease 8.6 %, 4.5 %, and 46.8 %, respectively; relative mortality decrease 22.0 %, 30.9 %, and 50.0 %, respectively). Early gastric cancer diagnosis increased over time for all countries. Net 1-year survival improved significantly between the two time periods in all countries, and at 5 years in Belgium and Portugal.Conclusions This is the first study comparing trends (2007–2016) in gastric cancer incidence and mortality in some European countries. We found an increasing proportion of T1 gastric cancers and a decrease in age-standardized mortality over time, supporting the use of secondary prevention strategies.